(untitled) - Tobin, James (Boston, Mass., 1998)
Graduate level text for courses & seminars in monetary theory. Based on materials from the author's graduate courses at Yale and M.I.T., these notes were revised and updated by the author over many years
Keywords: Money,Capital,Credit,TIền tệ,Vốn,Tín dụng